2018
DOI: 10.1538/expanim.18-0038
|View full text |Cite
|
Sign up to set email alerts
|

Increase in blood-brain barrier permeability does not directly induce neuronal death but may accelerate ischemic neuronal damage

Abstract: It is observed that the increase in blood-brain barrier (BBB) permeability (BBBP) is associated with ischemic stroke and thought to trigger neuronal damage and deteriorate ischemic infarction, even though there is no experimental proof. Here, we investigated the effect of BBBP increase on brain damage, using a combination of photochemically-induced thrombotic brain damage (PIT-BD) model, a focal brain ischemic model, and transient bilateral carotid artery occlusion model (CAO, a whole brain ischemic model), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…A number of previous studies have demonstrated that reactive gliosis due to various pathological conditions in the central nervous system increases permeability of the blood-brain barrier [20][21][22]. This can accelerate ischemic neuronal damage [23] and trigger inflammatory responses [24][25][26], which can exacerbate neuronal death [25]. Reactive gliosis commonly occurs following TFI, and in this process, glial cells (astrocytes and microglia) are hypertrophied with a thickened cellular structure [6,7,15].…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have demonstrated that reactive gliosis due to various pathological conditions in the central nervous system increases permeability of the blood-brain barrier [20][21][22]. This can accelerate ischemic neuronal damage [23] and trigger inflammatory responses [24][25][26], which can exacerbate neuronal death [25]. Reactive gliosis commonly occurs following TFI, and in this process, glial cells (astrocytes and microglia) are hypertrophied with a thickened cellular structure [6,7,15].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that chronic hypoxia could cause older rats to exhibit the characteristics of adult chronic hydrocephalus, including increased ventricular size, slightly increased intracranial pressure, and cognitive deficits in the brain 124 . Besides, free radicals, such as reactive oxygen species and reactive nitrogen species, are also associated with oxidative damage to neurons and other brain cells 125,126 . Oxidative stress induced by hypoxia/ischemia environment involving lipid peroxidation and oxidative and nitrosylative reaction may be one of the mechanisms of brain injury in hydrocephalus.…”
Section: Antioxidative Stress Treatment For Hydrocephalusmentioning
confidence: 99%
“…Physiological responses after stroke include BBB break down, delayed angiogenesis and neuron death (55). Previous studies have shown that neuronal damage in the central nervous system (CNS) is correlated with blood-brain barrier (BBB) breakdown (56)(57)(58). BBB is important for maintaining stability of the brain microenvironment of brain.…”
Section: Discussionmentioning
confidence: 99%